Proceedings of the 7th International Conference on Applied Research in Management, Economics and Accounting 2023
DOI: 10.33422/7th.iarmea.2023.07.101
|View full text |Cite
|
Sign up to set email alerts
|

The Change of Digital Marketing with Artificial Intelligence

İbrahim Halil Efendioğlu

Abstract: Artificial intelligence (AI) and machine learning technologies are increasingly gaining importance for accurately analyzing consumer behavior and delivering customized advertising content within digital marketing strategies. A rapid increase has been observed in the recent research concerning machine learning and artificial intelligence in the digital marketing literature. This research aims to strategically and thematically present a scientific map of publications using digital marketing, machine learning, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The integration of AI with marketing strategies enables the processing of massive amounts of information, identifies trends, predicts customer behavior (Khatri, 2021), leads to significant advancements in personalized messaging, enhances analytics, and more effective marketing strategies (Efendioğlu, 2023). Employing appropriate analytical techniques, online reviews play a crucial role in visitors' decision-making process and offer tour operators valuable strategic information about business performance (Oliveira et al, 2020).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The integration of AI with marketing strategies enables the processing of massive amounts of information, identifies trends, predicts customer behavior (Khatri, 2021), leads to significant advancements in personalized messaging, enhances analytics, and more effective marketing strategies (Efendioğlu, 2023). Employing appropriate analytical techniques, online reviews play a crucial role in visitors' decision-making process and offer tour operators valuable strategic information about business performance (Oliveira et al, 2020).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The findings in Figure 5.4 also revealed that paid advertising for web visibility has a moderate rating (x 2.8), suggesting that promoting the website by increasing its visibility in search engine results pages ( E P ) through paid advertising is not very high effective as some tour operators don't use this strategy. The use of AI driven predictive analytics to influence visitors' decision-making and personalized experiences is low ((x 0.5), implying that AI is not perceived by responded as one of the very effective elements of digital marketing strategies, which could be due to In the tourism market, the new digital environment and the use of social media show that tour operators must adopt new approaches and establish new marketing strategies such as integrating AI in digital marketing strategies (Efendioğlu, 2023;Khatri, 2021;Velentza & Metaxas, 2023) Figure 3: Applications of Marketing Strategies Tools by Tour Operators…”
Section: Applications Of Digital Marketing Strategies By Tour Operatorsmentioning
confidence: 99%
See 1 more Smart Citation